UPAYA MENINGKATKAN KETERAMPILAN MENULIS CERITA PENDEK MELALUI MODEL PROBLEM BASED LEARNING KELAS V SD INPRES BORONGUNTIA KABUPATEN GOWA: penelitian tindakan kelas - Nurul Zahra Aulia; Abdul Rahman Rahim; Tarman A. Arif (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Efforts to Improve Short Story Writing Skills Through Problem-Based Learning Models in Fifth Grade Students of SD Inpres Boronguntia, Gowa Regency. The main problem in this study is how to apply the Problem-Based Learning model in improving the short story writing skills of fifth grade students of SD Inpres Boronguntia, Gowa Regency. This study aims to improve short story writing skills with the Problem-Based Learning model in fifth grade students of SD Inpres Boronguntia, Gowa Regency. The results of the study showed that in the first cycle individually out of 16 students only 7 students or 43.75% met the Learning Objective Completion Criteria (KKTP) or were in the very low category. Classically it had not been met because the average value obtained was 66.56%. While in the second cycle of 16 students as many as 14 people or 87.5% had met the KKTP and classically it had been met, namely the average value obtained was 81.06% or was in the high category. Based on the results of the study above, it can be concluded that the short story writing skills of fifth grade students of SDN Boronguntia, Gowa Regency through the application of the Problem Based Learning model have increased.